Prostate-Specific Membrane Antigen Uptake and Survival in Metastatic Castration-Resistant Prostate Cancer - Vlachostergios, Panagiotis J.; Niaz, Muhammad Junaid; Sun, Michael; Mosallaie, Seyed Ali; Thomas, Charlene; Christos, Paul J.; Osborne, Joseph R.; Molina, Ana M.; Nanus, David M.; Bander, Neil H.; Tagawa, Scott T. (Frontiers in Oncology, 2021)
Background Prostate-specific membrane antigen (PSMA) imaging has been suggested as highly sensitive modality for detection of metastases in patients with biochemically recurrent or advanced prostate cancer (PCa). PSMA expression is associated with grade and stage and has a relationship with androgen receptor signaling. The aim of this study was to evaluate the prognostic utility of radiographic PSMA expression in men with metastatic castration-resistant prostate cancer (mCRPC). Methods Patients with mCRPC and available baseline PSMA imaging were studied. Images by planar/single-photon emission computed tomography (SPECT) or positron emission tomography (PET)/CT were reviewed. Planar/SPECT images were scored semi-quantitatively and PET/CT scored quantitatively with comparison of tumor uptake to liver uptake on a scale of 0–4 in order to determine an imaging score (IS). The IS (high: 2–4 versus low: 0–1), subsequent receipt of life-prolonging systemic therapies (taxane chemotherapy, potent androgen receptor pathway inhibitors, sipuleucel-T, and radium-223), and the CALGB prognostic risk stratification of patients were analyzed according to overall survival (OS) in univariate and multivariate Cox’s proportional hazards models. Results High PSMA expression (IS 2–4) was found in 179 (75.21%) patients, and 59 (24.79%) patients had low PSMA uptake. The median OS of the entire cohort was 16.8 (95%CI: 14.9–19.3) months. Patients with a high IS had a significantly shorter OS of 15.8 (95%CI 13.0–18.1) months compared to those with low expression [22.7 (95%CI: 17.7–30.7) months, p = 0.002]. After accounting for use of life-prolonging therapies (p<0.001) and CALGB prognostic groups (p = 0.001), high PSMA IS emerged as an independent prognostic factor for OS [HR(95%CI): 1.7 (1.2–2.2); p = 0.003]. Conclusion Presence of high radiographic PSMA expression on SPECT or PET/CT may portend a poor prognosis in patients with mCRPC treated with standard systemic therapies. This provides implications for therapeutic targeting of PSMA-avid disease as a means to improve outcomes.